The Early (Feminist) Essays of Victoria Ocampo - Doris Meyer (Studies in 20th & 21st Century Literature, 1996)
This study examines the essays written by Ocampo between 1920 and 1934, prior to the time when she publicly voiced her adhesion to feminism and the rights of women in Argentine society. In these works from her Testimonios in which Ocampo struggles to find her voice as a female writer, the maleable essay serves her need to engage in discursive dialogues from the margins of the literary culture of her time. Both as a woman and a member of the oligarchy, she questions cultural assumptions and gender-based binary structures common among the male writers of her time, many of whom she knew personally. Using rhetorical strategies that show the self-reflexive and subversive nature of her writing, Ocampo reads and reinterprets these works from a parenthetical feminist perspective, contesting their intellectual and aesthetic biases. The active agency of the reader as writer in these early essays shows Ocampo's awareness of her own unorthodox subject position—alienated from the conventions of her class, her gender, her national culture and language. Her autobiographical musings and her engagement with literary modernity in the 1920s and 1930s reveal a woman who accepted the liabilities of articulating an autonomous self, both in a European and a Latin American context. The influence of family bonds and patriarchal morality decisively shaped, but did not ultimately control, the way Victoria Ocampo eventually defined herself as a feminist author.
Keywords: Victoria Ocampo; feminism; feminist writings; women' s rights; Argentine literature; society; Testimonios; aesthetic bias; self; autobiography; autonomy; family